HSE July 2012 performance report. National service plan 2012. (Health Service Executive, 2012)
The Performance Report (PR) provides an overall analysis of key performance data from Finance, HR, Hospital and Primary & Community Services. The activity data reported is based on Performance Activity and Key Performance Indicators outlined in the National Service Plan 2012. P.16 Social Inclusion Total number in methadone treatment (M) The total number of clients in methadone treatment in June was 9,426 of this 93.4% were outside prisons and 6.6% (622) were in prisons. Of the 8,804 persons who are on methadone outside prison, the regional breakdown is as follows; • HSE DML – 5,006 • HSE DNE – 3,034 • HSE South - 448 • HSE West – 316 {For more information on methadone treatment figures see supplementary report, p.34; and expenditure on methadone mainanence, p.45]